Aplikasi Al-Auradul Maraqiyah Maraqitta’Limat Berbasis Android - Huswaton Hasanah; Muhammad Fahrurrozi; Akmaluddin (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2020)
The Maraqitta'limat Foundation is a Muslim foundation engaged in the field of da'wah, education and social society which was founded by TGH. Muhammad Zainuddin Arsyad. Like most other Muslim community organizations, the Maraqitta'limat Foundation has special zikir and prayers that are practiced for its members. The collection of zikir and prayers owned by the maraqitta'limat foundation is named Aurad, whose contents are taken from the Al-Quran and Hadits which are arranged in book form. The everyday Aurad learning process is applied by reading repeatedly through print media and then memorizing it. Given that currently the development of technology and information has influenced a person's learning behavior and style, an attractive and effective learning media is needed according to the needs of the times. In line with that, an android-based mobile zikir and prayer application that can be accessed on a smartphone is needed to support the needs of technological development. this time. This zikir and daily prayer application aims to make it easier for members of the Maraqitta'limat Foundation to learn and memorize the daily zikir and prayer recitations that are usually practiced at the maraqitta'limat foundation specifically and for Muslims in general.